Penerapan Pembiayaan Mudharabah Dalam Pengembalian Pembiayaan UMKM Syariah Di Desa Pematang Serai Kecamatan Tanjung Pura Kabupaten Langkat - Nasution, Nina Andriany, Miftha Rizkina (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The main purpose of this service is to find out the application of Mudharabah Financing in Refunding Sharia UMKM Financing in Pematang Serai Village, Tanjung Pura District, Langkat Regency. This service uses a qualitative descriptive approach. The main data source from field data by collecting data from informants in this case is the BUMDes. The results of the service show that the most important thing in mudharabah financing is the return of financing in the form of profit sharing from both parties according to sharia principles, especially fund managers. Because the profits that are shared are the results of operations (reveneu sharing) and net income (profit sharing). BUMDes savings and loans provide capital to MSME entrepreneurs to be used in running MSME businesses, and MSME actors as managers of these funds can increase MSME businesses by purchasing assets, developing business, increasing net income and generating high profits.